PENGATURAN DAN IMPLEMENTASI PELAYANAN DINAS SOSIAL TERHADAP FAKIR MISKIN DI KABUPATEN LEMBATA - Yohanes Paulus Sengaji Witak; Hernimus Ratu Udju; Megi O Radji (Petitum Law Journal, 2026)
This study investigates the way the Social Service of Lembata Regency regulates and implements services for people living in poverty using a social law approach. The findings show that although six main programs, Health Insurance Contribution Assistance Beneficiaries, Family Hope Program, Non-Cash Food Assistance, Direct Cash Assistance, Regional Health Insurance, Indonesia Smart College Card, have been implemented in accordance with national provisions (Permensos 262/2022) and SK Kadinsos No. 25/2024 with a fairly large reach (for example: 88,287 National Health Insurance recipients), its effectiveness is hampered by various factors both internal and external. From the internal side, the challenges faced include: (1) the absence of a specific regulation to address poverty, (2) a definition of poverty that is not in accordance with the local context, (3) inaccuracy of DTKS data (overlapping, including residents who are well-off or have died), (4) limited budget (the Joint Business Group program has not been implemented), and (5) uneven distribution of assistance (one District Social Welfare Worker, serves two sub-districts). From the external side, the main challenges are the mindset of community dependency (aid is used for non-basic consumer goods), minimal awareness of independence, and lack of cooperation from the community. This study recommends a comprehensive approach: strengthening regional regulations, updating technology-based data collection systems, increasing allocations from the Regional Government Budget, and integrating assistance that focuses on behavioral change.